PERFORMA BUDIDAYA UDANG VANAME (Litopenaeus vannamei) SEMI INTENSIF DI DESA PURWOREJO KECAMATAN PASIR SAKTI KABUPATEN LAMPUNG TIMUR - Luqman Hakim; Supono Supono; Yudha Trinoegraha Adiputra; Sri Waluyo (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
Pacific white shrimp (Litopenaeus vannamei) is new species were culture to replace tiger shrimp (Penaeus monodon) in Purworejo village, Pasir Sakti sub-district of East Lampung residence. This study was purposed to investigate culture performances of Pacific white shrimp in semi intensive system in two farmer groups. Eight ponds with ± 2100 m2/ ponds and density of 60 ind/m2 was used for this study. Results showed that Pacific white shrimp performances was different among two farmer groups. Sido Makmur group showed better performance compared to Lestari Gemilang with showed of ponds productivity 1337,8 kg and 1330,3 kg, respectively. FCR and SR among two groups also showed different, there were 1,88 to 2,39 and 86,95% to 63,3%, respectively. High mortality after WSSV infection was decreased pond productivity. Water quality parameters such as ammonia (0,029-0,031 ppm) and light density (<40 cm) were not suitable for shrimp culture impacted to pond productivity. WSSV infection and water quality parameters had corellation to pond performances.